Biosynthesis of silver nanoparticles with an antibacterial effect against Micrococcus luteus — the causative agent of nosocomial infections - Smirnov, O.E.; Zelena, P.P.; Yumyna, Yu.M.; Kalynovskyi, V.Ye.; Taran, N.Yu.; Schwartau, V.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
Green synthesis technologies offer effective tools for creating nanomaterials, which reduces the negative impact of chemical and physical methods to decrease the risks of nanotechnology. The manuscript proposes the biosynthesis of silver nanoparticles with antibacterial activity against Micrococcus luteus — an opportunistic pathogen that can cause nosocomial infections with aqueous extract of hot chili (Capsicum annuum L. ) variety Teja. Studies of biosynthesized nanoparticles were performed by UV-Vis spectroscopy, the size and morphology of nanoparticles were recorded by scanning electron microscopy. The effectiveness of biosynthesized nanoparticles against the growth and development of Micrococcus luteus has been established.